COVID-19 patient with coronary thrombosis supported with ECMO and Impella 5.0 ventricular assist device: a case report. Issue 6 (20th November 2020) - Valchanov, Kamen; Krishnan, Unni; Hoole, Stephen P; Davies, Will R; Pettit, Stephen; Jones, Nicola; Parmar, Jas; Catarino, Pedro; Osman, Mohamed; Berman, Marius
Abstract: Background: COVID-19 can present with cardiovascular complications. Case summary: We present a case report of a 43-year-old previously fit patient who suffered from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection with thrombosis of the coronary arteries causing acute myocardial infarction. These were treated with coronary stenting during which the patient suffered cardiac arrest. He was supported with automated chest compressions followed by peripheral veno-arterial extracorporeal membrane oxygenation (VA ECMO). No immediate recovery of the myocardial function was observed and, after insufficient venting of the left ventricle was diagnosed, an Impella 5 pump was implanted. The cardiovascular function recovered sufficiently and ECMO was explanted and inotropic infusions discontinued. Due to SARS-CoV-2 pulmonary infection, hypoxia became resistant to conventional mechanical ventilation and the patient was nursed prone overnight. After initial recovery of respiratory function, the patient received a tracheostomy and was allowed to wake up. Following a short period of agitation his neurological function recovered completely. During the third week of recovery, progressive multisystem dysfunction, possibly related to COVID-19, developed into multiorgan failure, and the patient died. Discussion: We believe that this is the first case report of coronary thrombosis related to COVID-19. Despite the negative outcome in this patient, we suggest that complex patients may in the future benefit from advanced cardiovascular support, and may even be nursed safely in the prone position with Impella devices.